2011
DOI: 10.1158/1535-7163.mct-11-0351
|View full text |Cite
|
Sign up to set email alerts
|

A6 Peptide Activates CD44 Adhesive Activity, Induces FAK and MEK Phosphorylation, and Inhibits the Migration and Metastasis of CD44-Expressing Cells

Abstract: The A6 peptide (acetyl-KPSSPPEE-amino) has antitumor activity in the absence of significant adverse events in murine tumor models and clinical trials. A6 shares sequence homology with CD44, an adhesion receptor involved in metastasis that is also a marker of cancer stem cells and drug-resistant phenotypes. We investigated the mechanism of action of A6 by examining its effects on CD44 activity, cell migration, and metastasis. A6 inhibited the migration of a subset of ovarian and breast cancer cell lines, exhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
74
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(74 citation statements)
references
References 34 publications
(31 reference statements)
0
74
0
Order By: Relevance
“…These results are in agreement with what was found very recently by Liu et al [24] using a sensitive Surface Plasmon Resonance (SPR) binding assay. Because the activity of A6 against CD44 was probed in cellular studies using DF1485 [25] , we also investigated the possibility of a direct interaction between the antibody and A6. For these studies we synthesized a 13 C labeled A6 peptide by introducing a 13 C methyl in its N-terminal acetyl group ( 13 C-A6 peptide).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are in agreement with what was found very recently by Liu et al [24] using a sensitive Surface Plasmon Resonance (SPR) binding assay. Because the activity of A6 against CD44 was probed in cellular studies using DF1485 [25] , we also investigated the possibility of a direct interaction between the antibody and A6. For these studies we synthesized a 13 C labeled A6 peptide by introducing a 13 C methyl in its N-terminal acetyl group ( 13 C-A6 peptide).…”
Section: Resultsmentioning
confidence: 99%
“…Next, we focused our studies on the binding properties of the A6 peptide given that it is in phase 2 clinical trials for CLL and SLL patients [9] (ClinicalTrials.gov Identifier: NCT02046928). The detailed mechanism of action of A6 has not been defined, but studies on metastatic disease suggested that it functions through a CD44-mediated pathway [25] . While cellular studies indicated a possible direct interaction between CD44 and A6, we could not observe any significant binding of A6 to 15 N-labeled sample of hCD44(21–178) in 2D [ 1 H, 15 N]-sofast-HMQC (Figure 2B) and ITC (supplementary Figure S1) experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Some new peptide inhibitors such as A-6 peptide [305] and P6 peptide [306] have recently been reported. A6 is a capped eight amino acid peptide (Acetyl-KPSSPPEE-NH2) derived from human urokinase plasminogen activator (uPA).…”
Section: Ha As Therapeuticmentioning
confidence: 99%
“…This peptide turned out to bind specifically to CD44 (Piotrowicz et al 2011) and is now examined in a trial phase II study for its efficacy in the treatment of human ovarian cancer (Ghamande et al 2008;Gold et al 2012). Another CD44 binding peptide, was identified in an indirect way, namely in a screen for overlapping synthetic peptides from the laminin α5 globular domain.…”
Section: Peptide-based Strategiesmentioning
confidence: 99%